ANALISIS TATA CARA PERHITUNGAN, PENYETORAN, PELAPORAN DAN PENCATATAN PPH PASAL 23 DAN PAJAK PERTAMBAHAN NILAI PT “X” - AINA MARSELINA; RIAN SUMARTA (Jurnal Bisnis dan Akuntansi, 2017)
The research is conducted with three basic purpose. The first purpose of this research is to find out the procedures of calculation, payment, reporting and recording of income tax article 23 and value added tax at PT. "X". The second purpose is to compare the suitability of the calculation, payment, and reporting process of Income Tax Article 23 to the taxation law number 36 year 2008 and value added tax to the taxation law number 42 year 2009. The last purpose is to compare the suitability of income tax article 23 and value added tax recording system at PT. "X" with the generally accepted accounting principles. The analytical procedure used is descriptive analysis method. The data acquired are output tax invoices, value added tax and income tax article 23 tax payment slip, value added tax and income tax article 23 return and accounting journal entries. The results of this research can be summarized as follows. First, calculation, payment and reporting income tax article 23 and value added tax in PT. "X" in accordance with the taxation rules. The second result of this research show that recording process of Income Tax article 23 and value added tax comply with generally accepted accounting principles.